Acrylic acid hydrogel as well as preparation method and application thereof
By using acrylic hydrogels composed of crosslinked polymers, arginine and glucose oxidase, the problems of poor water retention and unstable mechanical properties of existing hydrogel dressings in high temperature or high humidity environments are solved, and efficient wound healing and ooze absorption are achieved, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202510016540.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
The existing hydrogel dressings have poor water retention performance in high temperature or high humidity environments, unstable mechanical properties, insufficient surface adhesion, complex preparation process, high price, and limited ability to absorb and permeate.
Acrylic hydrogels composed of crosslinked polymers, arginine and glucose oxidase are used to form a stable three-dimensional network system through double bond polymerization and crosslinking, and release NO through enzymatic reactions in the human blood sugar environment to improve adhesion and mechanical properties.
It achieves excellent water retention and mechanical properties under high temperature or high humidity environments, improves surface adhesion and permeability absorption, simplifies the preparation process, reduces costs, and promotes wound healing through NO release.
Smart Images

Figure CN119868626A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical polymer materials, and in particular to an acrylic acid hydrogel and a preparation method and application thereof. Background Art
[0002] Ideal wound dressings have the function of promoting wound healing and avoiding wound infection. Traditional wound dressings are dry dressing materials such as sponges, absorbent gauze and absorbent cotton. Although they can protect wounds to a certain extent, their therapeutic effect is limited and they need to be replaced repeatedly, which not only aggravates the patient's pain, but also easily causes secondary damage to the wound. Hydrogels have been widely used in clinical practice as a new type of wound dressing. Hydrogels have a three-dimensional (3D) structure that can provide a moist healing environment for wounds by simulating the natural extracellular matrix (ECM) of the skin, thereby ensuring the moisture balance of the wound surface to improve wound healing. Compared with traditional dry dressing materials such as sponges, absorbent gauze and absorbent cotton, they have significant advantages in promoting wound healing, reducing pain and avoiding wound infection.
[0003] However, existing hydrogel dressings generally have the following problems: (1) Poor water retention: Existing hydrogels tend to release water-absorbing molecules under high temperature or high humidity environments, resulting in a significant decrease in their water absorption capacity. (2) Poor mechanical properties: When in a high humidity environment or when in use, the hydrophilic skeleton of existing hydrogels will continuously absorb water, causing the gel volume to expand and the mechanical properties to drop sharply, which in turn causes pressure or even damage to surrounding organs or tissues. (3) Poor surface adhesion: Existing hydrogel surfaces usually have no adhesion. When used as flexible materials, auxiliary tape is required to ensure a close fit with the tissue, which not only increases the complexity of use, but also leads to reduced stability, affecting the use effect. (4) Complex preparation process: Existing hydrogels need to go through a lengthy preparation process or use harsh preparation conditions to take into account the overall performance. (5) Limited ability to absorb exudate: Existing hydrogels cannot absorb a large amount of exudate when used on wounds with a lot of exudate, resulting in poor treatment effects and requiring frequent replacement. (6) High price: Existing hydrogels improve their bactericidal properties by adding antimicrobial agents, loading antimicrobial drugs, or using materials with antimicrobial activity. The use of these additives and special materials increases the manufacturing cost, resulting in a relatively high price for hydrogels. Therefore, it is urgent to develop a more efficient and stable hydrogel wound dressing that promotes wound healing, avoids wound infection, and has excellent adhesion, swelling, and exudate absorption properties. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an acrylic acid hydrogel and a preparation method and application thereof.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] In a first aspect, the present invention provides an acrylic hydrogel comprising a cross-linked polymer, arginine and glucose oxidase; the cross-linked polymer is formed by cross-linking N-acryloyl(trihydroxymethyl)aminomethane and acrylic acid; the molar ratio of N-acryloyl(trihydroxymethyl)aminomethane to the acrylic acid is 1:(1.5-12).
[0007] The acrylic hydrogel of the present invention comprises a cross-linked polymer, arginine and glucose oxidase, wherein the cross-linked polymer is obtained by a double bond polymerization reaction using acrylic acid and N-acryloyl (trihydroxymethyl) aminomethane as monomers to obtain a polymer chain, and the polymer is cross-linked by using the hydroxyl and carboxyl groups in its side chains as cross-linking points to form a stable three-dimensional network system, and by adding arginine and glucose oxidase, the hydrogel can be obtained by reacting with blood sugar to generate H2O2 under the blood sugar environment of the human body. The acrylic hydrogel of the present invention has excellent biocompatibility, degradability, and mechanical properties, and can exhibit good and adjustable adhesion in biomass materials by forming hydrogen bonds with the skin surface, and is suitable for use in the medical and biotechnology fields.
[0008] As a preferred embodiment of the acrylic hydrogel of the present invention, the molar ratio of the N-acryloyl(trihydroxymethyl)aminomethane to the acrylic acid is 1:(3-6).
[0009] Preferably, the molar ratio of the N-acryloyl(trihydroxymethyl)aminomethane to the acrylic acid is any one of 1:3, 1:4, 1:5, 1:6 or a range between the two.
[0010] As a preferred embodiment of the acrylic hydrogel of the present invention, the arginine is L-arginine.
[0011] In a second aspect, the present invention provides a method for preparing the acrylic hydrogel, comprising the following steps: dissolving N-acryloyl(trihydroxymethyl)aminomethane in a solvent to obtain an N-acryloyl(trihydroxymethyl)aminomethane solution, and then adding acrylic acid, an initiator, arginine and glucose oxidase, stirring, and reacting to obtain the product.
[0012] The preparation method of the acrylic acid hydrogel of the present invention optimizes the reaction conditions to make the reaction more sufficient and uniform, thereby improving the quality and performance of the prepared hydrogel, and the reaction operation of the present invention is greatly simplified, significantly reducing the post-processing process, shortening the production cycle, and improving the reaction efficiency. At the same time, on the one hand, the process does not require the addition of an additional cross-linking agent, the reaction conditions are mild, and the operation steps are simple, which avoids the toxicity and environmental pollution problems caused by traditional cross-linking agents; on the other hand, the effect of sustained release of NO can be achieved without the addition of an additional oxidant. In addition, the method of the present invention has excellent biocompatibility, degradability, mechanical properties, and can form hydrogen bonds with the skin surface to show good and adjustable adhesion in biomass materials, and is suitable for use in the fields of medicine and biotechnology.
[0013] As a preferred embodiment of the method for preparing the acrylic hydrogel of the present invention, the solvent is at least one of water, methanol, ethanol, dimethyl sulfoxide and dimethylformamide.
[0014] Preferably, the solvent is water; the volume ratio of the acrylic acid to the water is 1:4.
[0015] The inventors have found that if the proportion of water in the preparation method of the acrylic hydrogel of the present invention is too high, it is difficult to polymerize and cannot form a gel. If the proportion of acrylic acid is too high, the acrylic acid reaction is insufficient, which may cause hidden dangers in biological applications.
[0016] As a preferred embodiment of the method for preparing the acrylic acid hydrogel of the present invention, the molar ratio of the acrylic acid to the arginine is (20-40):1.
[0017] The inventors found that arginine acts as a polymerization inhibitor in the preparation method of the acrylic hydrogel of the present invention. If the proportion of arginine is too high, the acrylic hydrogel needs to be polymerized for a long time or the polymerization may fail. If the proportion of arginine is too low, the NO release capacity of the acrylic hydrogel will decrease.
[0018] Preferably, the molar ratio of the acrylic acid to the arginine is (25-30):1.
[0019] More preferably, the molar ratio of the acrylic acid to the arginine is any one of 25:1, 26:1, 27:1, 28:1, 29:1, 30:1 or a range value between two of them.
[0020] As a preferred embodiment of the method for preparing the acrylic hydrogel of the present invention, the molar ratio of the acrylic acid to the initiator is (350-420):1.
[0021] Preferably, the molar ratio of the acrylic acid to the initiator is any one of 350:1, 360:1, 370:1, 380:1, 390:1, 400:1, 410:1, 420:1, or a range value between two of them.
[0022] As a preferred embodiment of the method for preparing the acrylic hydrogel of the present invention, the initiator is ammonium persulfate.
[0023] As a preferred embodiment of the method for preparing the acrylic acid hydrogel of the present invention, the mass ratio of the acrylic acid to the glucose oxidase is (400-600):1.
[0024] Preferably, the mass ratio of the acrylic acid to the glucose oxidase is any one of 400:1, 500:1, 600:1, or a range value between the two.
[0025] As a preferred embodiment of the method for preparing the acrylic hydrogel of the present invention, the stirring time is 15 min-60 min, and the rotation speed is 300 rpm-800 rpm.
[0026] Preferably, the stirring time is any one of 15 min, 20 min, 30 min, 40 min, 50 min, 60 min or a range value between two of them, and the rotation speed is any one of 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm or a range value between two of them.
[0027] As a preferred embodiment of the method for preparing the acrylic hydrogel of the present invention, the reaction temperature is 45°C-60°C.
[0028] Preferably, the reaction temperature is any one of 45°C, 50°C, 55°C, 60°C, or a range between two of them.
[0029] In a third aspect, the present invention provides use of the acrylic hydrogel in a biological tissue adhesive.
[0030] The acrylic hydrogel of the present invention has excellent biocompatibility, does not induce rejection or adverse reactions with biological tissues or organs, and has excellent water retention, swelling, mechanical properties and good, adjustable adhesion, and can be used to prepare wound dressings or acute hemostatic materials to meet the needs of different biological tissues or organs to provide a moist, sterile healing environment for wounds, while maintaining sufficient strength and toughness to resist external pressure.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: first, the acrylic hydrogel of the present invention includes a network formed by double-bond polymerization and cross-linking of acrylic acid and N-acryloyl (trimethylol) aminomethane as monomers, arginine and glucose oxidase, which can continuously release NO, thereby promoting wound healing, reducing inflammation and regulating immune response. Secondly, the acrylic hydrogel of the present invention has excellent biocompatibility, degradability, water retention, swelling performance and mechanical properties, and can show good and adjustable adhesion in biomass materials by forming hydrogen bonds with the skin surface, and is suitable for preparing adhesives in the fields of medical and biotechnology. In addition, the preparation method of the acrylic hydrogel of the present invention greatly simplifies the reaction operation, significantly reduces the post-processing process, shortens the production cycle, and improves the reaction efficiency. And the preparation process does not need to add a cross-linking agent, the reaction conditions are mild, and the operation steps are simple; on the other hand, the effect of continuous release of NO can be achieved without adding an additional oxidant. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the Fourier transform infrared (FTIR) spectrum of the hydrogel of Verification Example 1 of the present invention;
[0033] Figure 2 This is a scanning morphology image of the hydrogel of Verification Example 2 of the present invention;
[0034] Figure 3 This is a NO release curve diagram of the hydrogel of Verification Example 3 of the present invention;
[0035] Figure 4 This is a dynamic strain scanning curve diagram of the hydrogel of Verification Example 4 of the present invention;
[0036] Figure 5 This is a dynamic frequency scanning curve diagram of the hydrogel of Verification Example 4 of the present invention;
[0037] Figure 6 This is a swelling rate curve of the hydrogel of Verification Example 5 of the present invention;
[0038] Figure 7 This is a water retention rate curve of the hydrogel of Verification Example 6 of the present invention;
[0039] Figure 8 This is a schematic diagram of the maximum pressure of the hydrogel in Verification Example 7 of the present invention;
[0040] Fig. 9 This is a schematic diagram of the hydrogel adhered to the wound on the surface of the pig stomach in Verification Example 8 of the present invention;
[0041] Fig.10 This is a compression strength curve of the hydrogel of Verification Example 9 of the present invention;
[0042] Fig.11This is a cyclic compression strength curve of the hydrogel of Verification Example 10 of the present invention;
[0043] Fig.12 This is a fluorescence image of live / dead cell staining of the hydrogel in Verification Example 11 of the present invention;
[0044] Fig.13 This is an analysis diagram of the adhesion of the hydrogel of Verification Example 12 of the present invention;
[0045] Fig.14 Schematic diagram of the gelation of the hydrogels of Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0046] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0047] The following is an elaboration in conjunction with specific embodiments to illustrate the practical effects of the solutions of the present invention.
[0048] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, equipment, etc. used, unless otherwise specified, can be obtained from commercial sources.
[0049] N-Acryloyl(trihydroxymethyl)aminomethane, CAS No.: 13880-05-2, purity: 97%, purchased from MacLean;
[0050] Acrylic acid, CAS number: 79-10-7, purity: 99%, density: 1.05g / cm 3 , purchased from McLean;
[0051] Ammonium persulfate, CAS number: 7727-54-0, purity: 99%, purchased from Aladdin;
[0052] L-arginine, CAS number: 74-79-3, purity: 98%, purchased from Maclean;
[0053] Glucose oxidase, CAS number: 9001-37-0, purity: 100 U / mg, purchased from Maclean.
[0054] Example 1: Preparation of hydrogel (1-ANG)
[0055] (1) 1.066 g (about 0.006 mol) of N-acryloyl (trimethylol) aminomethane (NAT) was dissolved in 20 mL of deionized water and stirred for 20 min at a stirring speed of 400 rpm to fully dissolve the N-acryloyl (trimethylol) aminomethane to obtain a N-acryloyl (trimethylol) aminomethane solution with a mass concentration of 0.053 g / mL;
[0056] (2) Take the N-acryloyl (trihydroxymethyl) aminomethane solution obtained in step (1), add 5 mL of acrylic acid (AA) (about 5.25 g, 0.073 mol), 0.04 g of ammonium persulfate (about 0.175 mmol), 0.5 g of L-arginine (about 2.87 mmol), and 0.01 g of glucose oxidase, and then stir at 50° C. for 25 min. The stirring speed is 400 rpm. After sufficient dissolution, the speed is reduced and the solution is allowed to stand for 30 min to obtain a hydrogel (1-ANG) based on acrylic acid that can release NO.
[0057] Example 2: Preparation of hydrogel (2-ANG)
[0058] The only difference between the preparation method of the hydrogel described in this example and that in Example 1 is that in step (1), 2.13 g of N-acryloyl (trihydroxymethyl) aminomethane (NAT) is dissolved in 20 mL of deionized water to obtain an N-acryloyl (trihydroxymethyl) aminomethane solution with a mass concentration of 0.107 g / mL.
[0059] Example 3: Preparation of hydrogel (3-ANG)
[0060] The only difference between the preparation method of the hydrogel described in this example and that in Example 1 is that in step (1), 3.20 g of N-acryloyl (trihydroxymethyl) aminomethane (NAT) is dissolved in 20 mL of deionized water to obtain an N-acryloyl (trihydroxymethyl) aminomethane solution with a mass concentration of 0.16 g / mL.
[0061] Example 4: Preparation of hydrogel (4-ANG)
[0062] The only difference between the preparation method of the hydrogel described in this example and that in Example 1 is that in step (1), 4.26 g of N-acryloyl (trihydroxymethyl) aminomethane (NAT) is dissolved in 20 mL of deionized water to obtain an N-acryloyl (trihydroxymethyl) aminomethane solution with a mass concentration of 0.213 g / mL.
[0063] Example 5: Preparation of hydrogel
[0064] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the molar ratio of N-acryloyl(trihydroxymethyl)aminomethane to acrylic acid is 1:1.5. However, the adhesion of the hydrogel in this example is reduced.
[0065] Example 6: Preparation of hydrogel
[0066] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the molar ratio of acrylic acid to L-arginine is 20:1. However, at this ratio, the hydrogel of this example completely gelled after 24 hours of polymerization.
[0067] Example 7: Preparation of hydrogel
[0068] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the molar ratio of acrylic acid to L-arginine is 40:1.
[0069] Example 8: Preparation of hydrogel
[0070] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the mass ratio of acrylic acid to glucose oxidase is 400:1.
[0071] Example 9: Preparation of hydrogel
[0072] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the molar ratio of acrylic acid to glucose oxidase is 600:1.
[0073] Example 10: Preparation of hydrogel
[0074] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the reaction temperature is 45° C. and the finished product of this example is completely gelled after being stirred for 10 hours.
[0075] Example 11: Preparation of hydrogel
[0076] The only difference between the preparation method of the hydrogel described in this example and that in Example 4 is that the reaction temperature is 60° C. and the finished product of this example is gelled after being stirred for 15 minutes.
[0077] Comparative Example 1: Preparation of hydrogel
[0078] The only difference between the preparation method of the hydrogel in this comparative example and that in Example 4 is that the molar ratio of N-acryloyl(trihydroxymethyl)aminomethane to acrylic acid is 1:0.1, and the finished product in this example cannot form a gel and has fluidity.
[0079] Comparative Example 2: Preparation of hydrogel
[0080] The only difference between the preparation method of the hydrogel described in this comparative example and that in Example 4 is that the molar ratio of N-acryloyl (trihydroxymethyl) aminomethane to acrylic acid is 1:20, and the finished product of this example cannot form gel and has fluidity.
[0081] Comparative Example 3: Preparation of hydrogel
[0082] The only difference between the preparation method of the hydrogel described in this comparative example and that in Example 4 is that the reaction temperature is 30° C., and the finished product of this example cannot form a gel.
[0083] Comparative Example 4: Preparation of hydrogel
[0084] The only difference between the preparation method of the hydrogel in this comparative example and that in Example 4 is that the reaction temperature is 70° C. The gelling speed of the finished product in this example is too fast and difficult to regulate.
[0085] Verification Example 1: Structural study of polymerization products in hydrogels
[0086] In this verification example, Fourier transform infrared (FTIR) spectroscopy was used to determine whether the polymerization reaction of acrylic acid (AA) and N-acryloyl (trihydroxymethyl) aminomethane (NAT) in the hydrogel of Example 1 was successful, and the chemical structure of the polymerization product was further studied.
[0087] Acrylic acid (AA), N-acryloyl (trihydroxymethyl) aminomethane (NAT) and the hydrogel product (ANG) obtained in Example 1 were freeze-dried and ground into powders, and infrared (FTIR) detection was performed.
[0088] like Figure 1 As shown, the characteristic absorption range of C=C double bond in FTIR spectrum is 1630cm -1 -1660cm -1 The range between 20 and 25 can be used to identify the presence of double bonds. Compared with the raw materials NAT and AA, the peak intensity of ANG in this range has decreased significantly. This phenomenon indicates that addition polymerization reaction occurred between NAT and AA, resulting in a decrease in the number of carbon-carbon double bonds in the product ANG.
[0089] Verification Example 2: Microstructure and morphology study of hydrogel
[0090] In this verification example, the microstructure and morphology of the hydrogel of Example 1 were studied by scanning electron microscopy.
[0091] The four hydrogels with different NAT concentrations obtained in Examples 1-4 were freeze-dried, vacuum-plated with gold, and the cross-sectional morphology of the hydrogels was observed using a Quanta 400FEG field emission scanning electron microscope produced by FEI / OXFORD / HKL.
[0092] like Figure 2 As shown, the hydrogels obtained in Examples 1-4 have a complex three-dimensional network structure, which is composed of many fine fibers or chain structures interwoven with each other, and the densification or porosity of the hydrogel network also changes to a certain extent as the NAT concentration changes.
[0093] Verification Example 3: Study on NO release ability of hydrogel
[0094] This verification example verifies the NO release ability of the hydrogels of Example 4 (4-ANG) and Example 7 through solution-level experiments, and evaluates their potential application value as NO-releasing materials by detecting the NO release amount of the hydrogels under specific conditions.
[0095] 0.5 g of the hydrogels of Examples 4 and 7 were added to a glass bottle containing 5 ml of a 6.0 mmol / L glucose solution, and the reaction was stirred. A certain amount of the hydrogel suspension was taken 0.5 h, 1.5 h, 3.5 h, 7.0 h, 27.5 h and 31.0 h after the start of the reaction to determine the amount of NO released.
[0096] like Figure 3 As shown, it can be seen from the NO release curve that the NO release amount of the hydrogel of the present invention gradually increases with the passage of time, which indicates that the hydrogel of the present invention has a stable NO release capacity.
[0097] Verification Example 4: Rheological properties test of hydrogel
[0098] In this verification example, the rheological properties of the four hydrogels prepared in Examples 1-4 were tested by a rotational rheometer to study their mechanical properties and structural characteristics.
[0099] Using Kinexus Pro from Malvern Instruments Ltd, UK + The rheological properties of hydrogels were tested using a rotational rheometer.
[0100] The fixture is a parallel plate with a diameter of 25 mm, the experimental temperature is 25° C., and the gap (Gap) of the parallel plate fixture is 1 mm.
[0101] (1) The hydrogel was subjected to dynamic strain scanning to determine the linear viscoelastic range of the hydrogel. The scanning frequency was fixed at 1 rad / s and the scanning range was 0.01%-100%.
[0102] (2) The sample was subjected to a dynamic frequency scan, with the strain fixed at 1% and the frequency scan range being 0.01 Hz-10 Hz.
[0103] like Figure 4As shown in the figure, with the increase of NAT concentration, the maximum linear viscoelastic region strain value of the sample increases, indicating that the increase in concentration increases the cross-linking points of the system and the formed network structure is denser.
[0104] like Figure 5 As shown, G' of the four hydrogel samples is always greater than G", which indicates that they exhibit solid properties and that the hydrogel has formed a relatively complete network structure with good mechanical stability and elasticity.
[0105] Verification Example 5: Study on the water absorption and swelling ability of hydrogel
[0106] In this verification example, the swelling rate of the four hydrogels prepared in Examples 1-4 was tested to study their water absorption and swelling capabilities.
[0107] The hydrogel sample was freeze-dried and dried in an oven at 40°C to constant weight. The mass W0 after drying was measured. The dried hydrogel sample was placed in a petri dish filled with deionized water to ensure that the sample was completely immersed. After immersion for different times, the hydrogel was taken out of the water, the surface water was absorbed with filter paper, the mass W1 of the hydrogel after water absorption was weighed, and the swelling ratio (Swellingratio) SR was calculated:
[0108]
[0109] like Figure 6 As shown, the hydrogel has continuous water absorption in the first 120 hours, and the swelling rate gradually increases. After 120 hours, the growth of the swelling rate tends to be moderate. After reaching the swelling equilibrium, the swelling rate is up to 250%, indicating that the hydrogel of the present invention has good water absorption and swelling ability, can maintain a certain stability and controllability during the water absorption process, and avoids the performance degradation caused by excessive water absorption. In addition, its moderate water absorption performance helps to keep the wound moist and promote wound healing, so that the hydrogel has potential application prospects and value in the fields of wound dressings, drug carriers, tissue engineering, etc.
[0110] Verification Example 6: Study on water retention properties of hydrogel
[0111] This verification example measures the mass changes of the four hydrogels prepared in Examples 1-4 after reaching swelling equilibrium to study their water retention properties.
[0112] Take the hydrogel that has reached swelling equilibrium in Example 6, absorb the surface water, measure the mass W2 of the hydrogel, put the hydrogel into an oven at 37°C, take it out after drying for different times, and weigh the mass W3 of the hydrogel, and calculate the water retention ratio WR of the hydrogel:
[0113]
[0114] like Figure 7 As shown, the hydrogel loses water quickly in the first 15 hours, then tends to slow down, reaches equilibrium between 20 hours and 60 hours, and the water retention is not less than 20%. This shows that the ANG hydrogel of the present invention has good water retention performance over a long period of time and can maintain a certain moisture content during use. As a wound dressing, it can effectively maintain a moist environment for the wound and promote wound healing.
[0115] Verification Example 7: Study on the Mechanical Properties of Hydrogel
[0116] In this verification example, a pressure burst test is performed at the tissue level to measure the pressure that the hydrogel of Example 1-2 can withstand, so as to study its pressure bearing capacity.
[0117] A 2 mm long incision was made on the surface of pig skin, and the two hydrogel samples prepared in Example 1 and Example 2 were adhered to the incision. A pressure of 0.5 KPa was applied for 1 min to ensure that the hydrogel was completely adhered to the pig skin surface. The device was in a completely closed state, and then air was slowly injected at a rate of 10 ml / min until the hydrogel burst. The test was repeated three times for each sample.
[0118] like Figure 8 As shown, the average bursting pressures that the two hydrogel samples can withstand are 0.0021MPa and 0.00253MPa, respectively, both of which are higher than the normal arterial blood pressure of adults (0.012MPa-0.018MPa). This result shows that the hydrogel samples of the present invention have sufficient pressure-bearing capacity, can remain stable within the normal arterial blood pressure range, and are not easy to rupture. The hemostatic material prepared using the hydrogel as raw material can effectively seal the wound, prevent blood loss, and play a hemostatic role.
[0119] Verification Example 8: Study on the bioadhesion and pressure bearing capacity of hydrogel
[0120] This verification example aims to verify the bioadhesion and pressure bearing capacity of the hydrogels of Examples 1-4 at the organ level.
[0121] The hydrogels of Examples 1-4 were adhered to the wound on the surface of the pig stomach, and deionized water was used to simulate the pressure that the pig stomach was subjected to.
[0122] like Fig. 9 As shown, the hydrogel can firmly adhere to the wound on the surface of the pig stomach, and under the pressure of deionized water, it shows good pressure bearing capacity without obvious shedding or damage. This result shows that the hydrogel of the present invention has excellent bioadhesion and pressure bearing capacity, and is expected to become a clinical application material for biological surface adhesives.
[0123] Verification Example 9: Compressive Strength Study of Hydrogel
[0124] This verification example aims to evaluate the compressive strength of the hydrogels of Examples 1-4 through a compression test.
[0125] (1) The hydrogel was made into a cylinder with a diameter of 20 mm and a height of 10 mm, and a compression test was performed on the hydrogel using a microcomputer-controlled electronic universal testing machine from Shenzhen Kobe Testing Equipment Co., Ltd.
[0126] Compression rate: 2 mm / min, the stress when the strain of the hydrogel sample is 70% is taken as the compression strength of the gel, and each sample is tested 3 times in parallel.
[0127] like Fig.10 As shown, the average compressive strength of the hydrogel of Example 4 reaches 420 Pa, which means that the hydrogel of Example 4 can better maintain its shape and integrity when under pressure, is less likely to deform or rupture, and has better mechanical properties.
[0128] Verification Example 10: Study on the compression recovery and anti-fatigue ability of hydrogel
[0129] This verification example aims to evaluate the compression recovery and fatigue resistance of the hydrogels of Examples 1-4 through cyclic compression tests.
[0130] The hydrogel that reached 70% strain in Example 9 was loaded with the same 2 mm / min rate until the pressure on the hydrogel cylinder was completely released and reached zero. This cyclic compression process simulated the recovery stage of the hydrogel after compression. This process was repeated five times in a row.
[0131] like Fig.11 As shown, through five consecutive compression-release cycles, the hydrogel can quickly and completely recover to its original shape and size, and with the increase in the number of cycles, the compression strength and recovery ability of the hydrogel do not decrease significantly. The hydrogel of the present invention can maintain a relatively stable morphology and modulus.
[0132] Verification Example 11: Study on Cell Biocompatibility of Hydrogel
[0133] In this verification example, the cell biocompatibility of the hydrogels of Examples 1-4 was evaluated by live / dead staining.
[0134] 1.0 mL of mouse fibroblasts (L929, density of 5000 cells / mL) were inoculated in hydrogel extracts with concentrations of 50 μg / mL, 100 μg / mL, and 200 μg / mL and cultured for 24 h, 48 h, and 72 h. At the predetermined time point, the cells were stained with a Calcein-Am / PI double staining kit for 10 min, and fluorescence images were obtained using a LSM710NLO confocal microscope from Zeiss, Germany.
[0135] like Fig.12 As shown, the propidium iodide image shows that the cells are not dead, which indicates that the hydrogel of the present invention has low cytotoxicity and the cells can grow and proliferate normally in the hydrogel extract.
[0136] Verification Example 12: Adhesion study of hydrogel
[0137] A lap shear test was performed using a microcomputer-controlled electronic universal testing machine (Kobe Testing Equipment Co., Ltd., Shenzhen) to evaluate the adhesion strength of aerogels on the surfaces of various materials. Fresh pigskin was adhered to a tinplate sheet using a cyanoacrylate adhesive to ensure that the pigskin did not deform during the experiment. The pigskin surface was then moistened with deionized water, and the samples of Example 3 (Sample 1), Example 4 (Sample 2), and Example 5 (Sample 3) were placed between two pieces of pigskin, with the contact area controlled to be 25 mm × 20 mm. Then the stretching was performed at a constant tensile rate of 0.2 mm / min. Each sample was repeated at least three times. The adhesion strength was calculated by the following formula:
[0138]
[0139] Where F is the maximum tensile stress (N); S is the hydrogel binding area (cm 2 ).
[0140] like Fig.13 As shown, the hydrogel of Example 5, as the degree of cross-linking increases, the surface solidifies and becomes hard, and its adhesion decreases significantly.
[0141] Verification Example 13: Hydrogel
[0142] like Fig.14 As shown, the hydrogels prepared by the preparation methods of Comparative Examples 1-3 were all unable to gel.
[0143] It can be seen that the present invention includes an acrylic acid hydrogel of a cross-linked polymer, arginine and glucose oxidase formed by double-bond polymerization and cross-linking of acrylic acid and N-acryloyl (trimethylol) aminomethane as monomers, which can continuously release NO, thereby promoting wound healing, reducing inflammation and regulating immune response. Secondly, the acrylic acid hydrogel of the present invention has excellent biocompatibility, degradability, water retention, swelling performance and mechanical properties, and can show good and adjustable adhesion in biomass materials by forming hydrogen bonds with the skin surface, and is suitable for preparing adhesives in the fields of medical treatment and biotechnology. In addition, the preparation method of the acrylic acid hydrogel of the present invention greatly simplifies the reaction operation, significantly reduces the post-processing process, shortens the production cycle, and improves the reaction efficiency. And the preparation process does not need to add a cross-linking agent on the one hand, the reaction conditions are mild, and the operation steps are simple; on the other hand, the effect of sustained release of NO can be achieved without the need to add an oxidant.
[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An acrylic acid hydrogel, characterized in that: The invention comprises a cross-linked polymer, arginine and glucose oxidase; the cross-linked polymer is formed by cross-linking N-acryloyl (trihydroxymethyl) aminomethane and acrylic acid; the molar ratio of the N-acryloyl (trihydroxymethyl) aminomethane to the acrylic acid is 1: (1.5-12).
2. The acrylic hydrogel according to claim 1, characterized in that The molar ratio of the N-acryloyl(trihydroxymethyl)aminomethane to the acrylic acid is 1:(3-6).
3. The method for preparing the acrylic hydrogel according to claim 1, characterized in that: The method comprises the following steps: dissolving N-acryloyl (trihydroxymethyl) aminomethane in a solvent to obtain an N-acryloyl (trihydroxymethyl) aminomethane solution, adding acrylic acid, an initiator, arginine and glucose oxidase, stirring, reacting, and obtaining the solution.
4. The method for preparing acrylic acid hydrogel according to claim 3, characterized in that: The molar ratio of the acrylic acid to the arginine is (20-40):
1.
5. The method for preparing acrylic acid hydrogel according to claim 4, characterized in that: The molar ratio of the acrylic acid to the arginine is (25-30):
1.
6. The method for preparing acrylic hydrogel according to claim 3, characterized in that: The mass ratio of the acrylic acid to the glucose oxidase is (400-600):
1.
7. The method for preparing acrylic hydrogel according to claim 6, characterized in that: The mass ratio of the acrylic acid to the glucose oxidase is 525:
1.
8. The method for preparing acrylic hydrogel according to claim 3, characterized in that: The reaction temperature is 45°C-60°C.
9. The method for preparing acrylic hydrogel according to claim 8, characterized in that: The reaction temperature was 50°C.
10. Use of the acrylic hydrogel according to claim 1 or 2 in biological tissue adhesive.